Lactate Shuttles in Neuroenergetics—Homeostasis, Allostasis and Beyond - Mason, Shayne (Frontiers in Neuroscience, 2017)
Understanding brain energy metabolism — neuroenergetics — is becoming increasingly important as it can be identified repeatedly as the source of neurological perturbations. Within the scientific community we are seeing a shift in paradigms from the traditional neurocentric view to that of a more dynamic, integrated one where astrocytes are no longer considered as being just supportive, and activated microglia have a profound influence. Lactate is emerging as the ‘good guy’, contrasting its classical ‘bad guy’ position in the now superseded medical literature. This review begins with the evolution of the concept of ‘lactate shuttles’; goes on to the recent shift in ideas regarding normal neuroenergetics (homeostasis) — specifically, the astrocyte–neuron lactate shuttle; and progresses to covering the metabolic implications whereby homeostasis is lost — a state of allostasis, and the function of microglia. The role of lactate, as a substrate and shuttle, is reviewed in light of allostatic stress, and beyond — to a state of allostatic overload (neuropathology), in terms of physical brain trauma, and reflected upon with respect to neurodegenerative diseases. Finally, the recently proposed astrocyte–microglia lactate shuttle is discussed in terms of chronic neuroinflammatory infectious diseases, using tuberculous meningitis as an example. The novelty extended by this review is that the directionality of lactate, as shuttles in the brain, in neuropathophysiological states is emerging as crucial in neuroenergetics.